Development of Interactive Learning Media Based on Google Sites Application Using the ADDIE Model for Arabic Language Instruction.: Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Google Sites Model ADDIE Untuk Pembelajaran Bahasa Arab - Sorongan, Asri Ainun; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2023)
This study presents a novel approach to Arabic language instruction through the creation of interactive learning media using the Google Sites application, guided by the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The goal of the research is to develop effective and engaging digital resources for Arabic language learners. The study utilizes a design-based research methodology, incorporating iterative cycles of design, development, and evaluation. Results indicate that the developed interactive learning media significantly enhance learners' engagement and comprehension of Arabic language concepts. Implications suggest that such innovative instructional materials offer a promising avenue for language educators to enhance the quality of language learning experiences and promote better student outcomes in language acquisition. Highlights: Innovative Approach: This study introduces an innovative method of language instruction by creating interactive learning media using the Google Sites application, guided by the systematic ADDIE model. Enhanced Engagement: The research highlights the development of interactive digital resources that significantly enhance learners' engagement and comprehension of Arabic language concepts, fostering a more dynamic learning experience. Pedagogical Implications: The findings underscore the potential of interactive digital tools to transform language education, suggesting implications for educators to optimize language learning through the integration of innovative instructional technologies. Keywords: Interactive learning media, Google Sites application, ADDIE model, Arabic language instruction, Language acquisition